2016
DOI: 10.1073/pnas.1604820113
|View full text |Cite
|
Sign up to set email alerts
|

Power in everyday life

Abstract: How does power manifest itself in everyday life? Using experiencesampling methodology, we investigated the prevalence, sources, and correlates of power in people's natural environments. Participants experienced power-relevant situations regularly, though not frequently. High power was not restricted to a limited few: almost half of the sample reported experiencing high-power positions. Positional power and subjective feelings of power were strongly related but had unique relations with several individual diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 52 publications
9
104
0
Order By: Relevance
“…However, research measuring and manipulating subjective feelings of power finds mixed results. For example, Smith and Hoffmann (2016) tracked individuals' experiences over a three-day period finding an association between high power and elevated mood, and low power and depressed mood, in keeping with a number of previous studies (Anderson & Berdahl, 2002, Study 1;Berdahl & Martorana, 2006;Bombari, Schmid Mast & Bachmann, 2017;Hecht & LaFrance, 1998;Langner & Keltner, 2008;Strelan, Weick & Vasiljevic, 2014;Weick & Guinote, 2008, Study 4;Weick & Guinote, 2010, Study 4;Wojciszke & Struzynska-Kujalowicz, 2007).…”
supporting
confidence: 62%
“…However, research measuring and manipulating subjective feelings of power finds mixed results. For example, Smith and Hoffmann (2016) tracked individuals' experiences over a three-day period finding an association between high power and elevated mood, and low power and depressed mood, in keeping with a number of previous studies (Anderson & Berdahl, 2002, Study 1;Berdahl & Martorana, 2006;Bombari, Schmid Mast & Bachmann, 2017;Hecht & LaFrance, 1998;Langner & Keltner, 2008;Strelan, Weick & Vasiljevic, 2014;Weick & Guinote, 2008, Study 4;Weick & Guinote, 2010, Study 4;Wojciszke & Struzynska-Kujalowicz, 2007).…”
supporting
confidence: 62%
“…Yet, hostile sexism has been disproportionally examined from an intergroup perspective, including investigating the ways men try to protect their advantaged societal position (Glick & Fiske, 1996Glick et al, 1997). The focus on women as outgroup members who contest men's advantaged societal-level power overlooks one of the most threatening contexts that challenges the power, dependence and gender-related concerns central to hostile sexism-heterosexual intimate relationships Overall & Hammond, 2018;Smith & Hofmann, 2016). Men and women deeply affect one another on a daily basis within intimate relationships, and thus hostile sexism is likely to have a particularly prevalent, routine and damaging impact on women.…”
Section: Implications For Understanding the Effects Of Sexist Attitudmentioning
confidence: 99%
“…Additionally, scholars have recently suggested that the relationship between power and social distance may be bidirectional (Trope & Liberman, ), therefore we felt that manipulating powerlessness could help enhance causal inferences. However, we encourage future research to replicate our findings measuring naturally occurring fluctuations in powerlessness (e.g., Smith & Hofmann, ).…”
Section: Discussionmentioning
confidence: 61%
“…To this point, a recent review of the power literature found that only 0.8% of the reviewed studies focused on powerlessness explicitly (Schaerer et al., ). This is an important shortcoming because research shows that most employees typically experience both powerfulness and powerlessness each day at work (Smith & Hofmann, ), and that the pyramid‐like structure of most organizations likely makes the experience of powerlessness far more common than the experience of powerfulness (Schaerer et al., ). Yet, despite the ubiquitous nature of experienced powerlessness, its organizational implications are not well understood (Schaerer et al., ).…”
Section: Introductionmentioning
confidence: 99%